Education Policy for Equalization: An Analysis of Higher Education Opportunities in Indonesia - Rifa'i, Andi Arif (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
Education is the right of every citizen and does not look at differences in status such as; ethnicity, race, religion or social class. This right was explicitly stated in the mandate of Article 31 of the Republic of Indonesia Constitution. The mandate was realized with a budget allocation of 20% of the National Budget for the benefit of Education. Equal distribution of Education opportunities, by providing opportunities to underprivileged children through a scholarship program, the fact is not yet fully able to answer the issue of the quality of the nation's human resources. Program acceleration and innovation are needed to ensure that higher education opportunities are open, which in turn has an impact on improving the quality of human resources and the nation's competitiveness.